Influence of electrochemical reduction of selfdoping on the low temperature crystallization and photocatalytic activities of TiO2 nanotubes. (27th August 2019) - Nair, Sinitha B; K, Aijo john; Menon, Sumithra S; Rahman, Hilal; Joseph, Julie Ann; Shaji, Sadasivan; Philip, Rachel Reena
Abstract: Cost effectiveness and reducing the energy and time consumption are crucial factors of concern while material preparation for device fabrication is considered. Here a simple electro chemical reductive method of self-doping is proved for first time to achieve efficient ultrafast (5 s) low temperature (15 °C) crystallization of well aligned TiO2 nanotubes (TONT). Moreover, the so prepared self-doped TONTs are demonstrated to exhibit superior photocatalytic performance over the undoped in the degradation of the organic pollutant methylene blue. The effect is correlated with the tailoring of the crystallinity and red shift in band gap on self-doping due to the introduction of Ti 3+ ions and oxygen vacancies.